2002
DOI: 10.1262/jrd.48.287
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mongolian Gerbil 1-cell Embryos to Blastocysts in Co-culture with Oviductal Cells in TCM 199 Supplemented with Pyruvate, Lactate and Fetal Calf Serum.

Abstract: Abstract.To develop an in vitro culture system for Mongolian gerbil embryos, we examined the effect of co-culture with oviductal epithelial cells on the development of 1-and 2-cell embryos collected from superovulated gerbils. In the first experiment, 2-cell embryos were cultured in modified TCM 199 supplemented with pyruvate, lactate and fetal calf serum (mTCM199) with or without gerbil or mouse oviductal cells. In the second experiment, in 1-cell embryos were cultured with or without gerbil oviductal cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In a previous report, 1-cell gerbil embryos were blocked at the 16-cell stage when they were cultured in modified M16 [3] and modified TCM199 [2]. These results correspond to the result of this protein synthesis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In a previous report, 1-cell gerbil embryos were blocked at the 16-cell stage when they were cultured in modified M16 [3] and modified TCM199 [2]. These results correspond to the result of this protein synthesis.…”
Section: Discussionsupporting
confidence: 60%
“…We reported that Mongolian gerbil 1-cell embryos can develop in vitro to blastocysts in coc u l t u r e w i t h o v i d u c t c e l l s i n T C M 1 9 9 supplemented with pyruvate, lactate and fetal bovine serum [2], but could not be developed consistently to the blastocyst stage in a chemically defined medium in vitro [3]. Also, Mongolian gerbil 2-cell embryos developed in vitro to the 16-cell stage [3].…”
mentioning
confidence: 99%
“…Some researchers have tried to let gerbil embryo develop into blastocyst in vitro, but were unable to produce any remarkable results. This is because the cell block prevents the gerbil embryo development to the blastocyst stage in vitro [15,16]. There is no report on growth factor IGF-I receptors begin to be concurrently expressed at the compaction of the mouse embryos [17].…”
Section: Discussionmentioning
confidence: 99%